ANALYSIS OF THE POSSIBILITIES OF INCLUSIVE DEVELOPMENT TERRITORIAL COMMUNITIES UNDER THE CONDITIONS OF THE STATE OF MARTIAL (Economic journal of Lesya Ukrainka Volyn National University, 2023)
Introduction. The development of territorial communities to ensure the quality of life for their residents remains a relevant direction for scientific research. At the same time, opportunities for development initiatives differ between territorial communities after the completion of decentralization reforms and depend on their proximity to active conflict zones.The purpose of the article. Conducting an analysis of the opportunities for inclusive development of territorial communities, taking into account the limited resources of local budgets.Results. Based on the analysis results, the focus was on the current state of theoretical research on various aspects of inclusive development in territorial communities. In particular, it was established that inclusive growth has broader objectives compared to gross domestic product growth. The essence of inclusive development is to improve the well-being of residents in territorial communities, reduce poverty and inequality, and increase the involvement and active participation of people in the economy. An analysis was conducted on the impact of the completion of decentralization reform in Ukraine in 2020 and the onset of hostilities in 2022 on the revenues and expenditures of local budgets in Volyn Oblast. Changes in the structure of local budget revenues were studied, including an increase in the share of own revenues and a decrease in the proportion of transfers from the state budget.Conclusiоns. The decentralization reform has a positive impact on the ability of territorial communities to carry out development expenditures from local budgets. However, while the capacity of territorial communities to meet the needs of local development has increased after the completion of the reform, it has been significantly complicated under the conditions of armed aggression by the Russian Federation. The impact of martial law on the indicators of revenues and expenditures of local budgets in the Volyn region has been confirmed, as well as the increased consequences of the impact of military operations on the indicator of own revenues of local budgets in the proximity of active combat zones. There is a need for further research on the theoretical and institutional possibilities of inclusive development of territorial communities, considering the limited resources of local budgets and the growing demands for expenditures due to the war.
Keywords: inclusive development, territorial communities, local budgets, decentralization, martial law